Fraction of spectral solar irradiance transmitted through snow and sea ice as measured in different depths under sea ice (transmittance) at station PS122/4_45-61 on 2020-07-01, survey 1, version 2.0 - Philipp Anhaus; Stefanie Arndt; Christian Katlein; Daniela Krampe; Benjamin Allen Lange; Ilkka Matero; Julia Regnery; Jan Rohde; Martin Schiller; Marcel Nicolaus (PANGAEA, 2025)
Transmitted solar irradiance was measured using an ACC (Advanced-Cosine-Collector) RAMSES hyper-spectral radiometer (TriOS) mounted on the ROV during the MOSAiC expedition between November 2019 and September 2020 and normalized by the incident solar irradiance as measured using an ACC RAMSES hyper-spectral radiometer (TriOS) installed on the sea ice. All times are given in Universal Coordinated Time (UTC).
In: Anhaus, P et al. (2025): Spectral solar radiation over and under sea ice during the MOSAiC expedition 2019/20, version 2.0 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.979856